THE IMPORTANCE OF CULTURAL AWARENESS IN THE FIELD OF TRANSLATION (Web of Teachers: Inderscience Research, 2025)
Cultural awareness plays a crucial role in the field of translation, as language and culture are deeply interconnected. A translator must not only have linguistic proficiency but also understand cultural nuances, traditions, and values to ensure an accurate and meaningful translation. This article explores the importance of cultural awareness in translation, highlighting its impact on accuracy, context preservation, and intercultural communication.